2003
DOI: 10.1115/1.1563241
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Low-Emission GE-7FDL High-Power Medium-Speed Locomotive Diesel Engine

Abstract: This paper summarizes the technical development of the low-emission GE-7FDL series locomotive diesel engine. The development focused on reducing the engine exhaust NOx emission significantly while reducing and curbing other visible and nonvisible emissions with minimal adverse impact on the engine fuel efficiency and minimal changes to the engine system and components. Concepts were analyzed, and were investigated using a single-cylinder 7FDL research engine. A low-emission 16-cylinder 7FDL engine and a GE loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Two other technologies that were used to meet Tier 0 requirements were increasing the compression ratio and modifying the cylinder liner and piston rings to reduce lubricating oil consumption. EPA had expected compression ratio changes to be introduced for compliance with Tier 1, but GE did so for Tier 0 as well (Chen, Flynn, Gallagher, & Dillen, 2003).…”
Section: Methods Of Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…Two other technologies that were used to meet Tier 0 requirements were increasing the compression ratio and modifying the cylinder liner and piston rings to reduce lubricating oil consumption. EPA had expected compression ratio changes to be introduced for compliance with Tier 1, but GE did so for Tier 0 as well (Chen, Flynn, Gallagher, & Dillen, 2003).…”
Section: Methods Of Compliancementioning
confidence: 99%
“…Rather, they were likely used to minimize the loss in fuel economy from retarding injection timing to meet the NOx standards. In addition, EF&EE reports that new Tier 0 locomotives (Models C and E) used split cooling (Uzkan & Lenz, 1999), increased compression ratios, and combustion chamber design, and Chen et al (2003) comment in their conclusions that the same technology package can also be used to upgrade baseline engines to the same standards. As with EFI, EF&EE expects that it was not strictly necessary to add split cooling in order to meet the standards.…”
Section: Methods Of Compliancementioning
confidence: 99%
“…Therefore, emission factors for the 2009 inventory were taken from the EPA's AP-42 (EPA, 2011a) and literature data for similarly sized engines used in diesel-electric locomotives and diesel generators (e.g., Shah et al, 2006;Sawant et al, 2007;Chen et al, 2003). The NONROAD model (EPA, 2008) was not used to estimate emission factors because it estimates point values and not distributions.…”
Section: Drillingmentioning
confidence: 99%
“…All research reported on locomotive engines has evaluated the engine at pre-determined notches. 1217 Accordingly, engine performance, emissions and combustion measurements in the present research is also carried out on these nine pre-determined engine notches. The experiments were performed three times for each engine operating point and the average reading was used for further data analysis.…”
Section: Test Pointsmentioning
confidence: 99%